Gender-Based Violence and Criminal Law Enforcement in South Africa: Challenges and Legal Reform Perspectives - Themba Mokoena Sithole; Kagiso Rabada; Ayanda Thandeka Buthelez; Lerato Naledi Sekgobela; Thabo Mbeki; Cyril Ramaphosa; Nomsa Khanyisa Cele (Journal of Multidisciplinary Law Studies, 2026)
Gender-based violence remains a pervasive and deeply rooted challenge in South Africa, posing serious threats to human rights, public safety, and social justice. Although previous studies have extensively discussed gender-based violence in South Africa, limited scholarship has critically examined the gap between progressive criminal law reforms and their practical enforcement within justice institutions. Using a normative juridical approach combined with qualitative content analysis, the study critically evaluates statutory regulations, judicial decisions, and policy frameworks to assess the gap between legal norms and enforcement practices. The findings demonstrate that weak institutional coordination, inadequate law enforcement training, patriarchal bias, and resource limitations significantly undermine the implementation of victim-centered legal protections and access to justice. Structural inequalities, patriarchal norms, and resource constraints further weaken the criminal justice response. The article argues that strengthening institutional coordination, improving police accountability, and enhancing victim support mechanisms are essential for effective enforcement. It also highlights the importance of integrated legal reforms that combine punitive measures with preventive and restorative approaches. The study contributes to socio-legal debates by challenging the assumption that punitive criminal law alone can effectively address gender-based violence without institutional transformation and broader socio-cultural reform. The study concludes that effective responses to gender-based violence require an integrated framework combining legal enforcement, institutional accountability, victim-centered justice, and long-term socio-cultural transformation.